Determinan Penanganan Limbah Medis oleh Petugas Cleaning Service di Rumah Sakit Sansani Kota Pekanbaru - Aria Gusti; Desri Resfita; Putri Nilam Sari (HB PRESS, 2022)
As contributors to infectious waste, hospitals become one of the diseases transmission routes and health risks for their workers. Negligence of CS using PPE is still often found in the handling of medical waste. This study aimed to determine the factors related to medical waste handling by CS at Sansani Hospital in Pekanbaru City in 2021. This study was quantitative with a cross-sectional approach and performed at the Sansani Hospital Pekanbaru from December 2020 to March 2021. The population of this study was 30 cleaning services and using total sampling as the sample. Processing data using univariate and bivariate analysis with chi-square test. This study showed that 43,3% of cleaning services had a lack of waste medical handling, 26,7% had a lack of knowledge, 26,7% had a negative attitude, 40% had a poor perception of availability of facilities, and 33,3% had a poor perception to supervision. There was statistically significant relationship between attitude (p-value < 0,049), availability of facilities (p-value = 0,001), and supervision (p-value < 0,000) with medical waste handling. There was no relationship between knowledge (p-value = 0,698) with medical waste handling. Attitudes, availability of facilities, and supervision were the factors related to cleaning services in medical waste handling. It is suggested that Sansani Hospital Pekanbaru improve field supervision, provide socialization and training in medical waste management and equip waste management facilities, especially for PPE, such as gloves, safety boots, and medical waste labels.